The education and training of future hip preservation surgeons: aggregate recommendations of high-volume surgeons - Chen, Austin W (J Hip Preserv Surg, 2018)
Hip preservation is one of the fastest growing subspecialties in orthopaedic surgery. Surgical training recommendations and guidelines in this field are lacking. To survey high volume hip preservation surgeons regarding their perspectives on the current and future training of surgeons entering their field, a cross-sectional survey of 16 high-volume hip preservation surgeons was conducted to gather perspectives and opinions on the most appropriate education of future hip preservation surgeons. All participants completed the survey in person and anonymously. Of the surveyed surgeons, the mean career hip preservation volume was 1031.25 cases (250 to >3000) with an average annual volume of 162.08 cases (75–400). The average number of hip arthroscopy cases necessary to competently perform joint access is 19, labral repair is 34, acetabuloplasty/femoroplasty are 54, labral reconstruction is 101 and capsular closure/plication is 53. Fifty-six percent of the surgeons believe mid-career surgeons who have never performed hip preservation surgery should not adopt it as part of their practice. The mean optimal number of cases recommended was 128 hip arthroscopies during a dedicated hip preservation fellowship and 67 hip arthroscopies during a sports medicine fellowship. Surgeons with an interest in hip preservation careers, should strongly consider a 12-month dedicated hip preservation fellowship that provides exposure to at least 128 cases, including open and arthroscopic techniques, hip arthroplasty, and research opportunities. Mid-career surgeons should be cautious about adopting hip preservation into their practice if they have not had prior adequate training.